21st-century competences and learning that technical and vocational training - Le, Sai Kham; Hlaing, Su Nandar; Ya, Kyaw Zay (Researcher and Lecturer Society, 2022)
The 21st century is characterized by rapid developments in information technology and automation, with many routine and repetitive jobs being replaced by machines, both production and computers. The world of his technical and vocational education curriculum in the 21st century is full of challenges to face. Technical education and vocational education must be able to create learning that is able to make students have the competencies needed by the world of work in the 21st century. Technological developments make changes in economic, social culture and including education. This article aims to examine the competencies needed in the 21st century and how effective learning is for this century. The research was conducted using the literature review method. In the 21st century, the world of work is increasingly complex, graduate students from technical education and vocational education must have learning skills, literacy skills and life skills. Skill competencies taught to students must focus on one particular area, because in the world of work each worker will only do one type of work. Learning in technical and vocational education is recommended to use the application of the project-based learning model. Various research results have found that this model is able to make students have the skills needed in this 21st century.